Histological and histochemical changes of the skeletal muscle in human chronic Chagas' disease - Analia Taratuto; M. A. Pagano; Teresa Fumo; Olga P. Sanz; R. E. P. Sica (Arquivos de Neuro-Psiquiatria)
Gastrocnemius muscle biopsies were performed in 7 subjects with chronic Chagas' disease. On clinical and laboratory grounds the selected patients were judged to be healthy, being the only abnormality found the presence of positive serum tests for Chagas' disease. Fibre type grouping of either type I or type II was observed in 5 of the 7 patients. Furthermore, in 2 of the 5 patients showing muscle fibre groupings, angular fibres reacting with NADH and non-specific sterase were also found. These observations strongly suggest denervation associated with reinervation. This picture often can be observed in the skeletal muscle of patients with well compensated denervatory conditions who do not show clinical evidences of denervation.